2019
DOI: 10.1038/s41379-018-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Presence of tertiary lymphoid structures determines the level of tumor-infiltrating lymphocytes in primary breast cancer and metastasis

Abstract: The level of tumor-infiltrating lymphocytes and presence of tertiary lymphoid structures are significant prognostic and predictive factors in primary breast cancer. However, the understanding about differences in tumor-infiltrating lymphocytes and tertiary lymphoid structures at various metastatic sites or between primary breast tumors and metastatic sites is limited. A total of 335 cases of metastatic breast cancer from four metastatic sites (lung, liver, brain, and ovary) were included. We analyzed the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 33 publications
5
65
0
Order By: Relevance
“…This is notably the case for tumours occurring in immunologically privileged sites, such as the brain (glioblastoma and lower-grade glioma) and the eye (uveal melanoma), although tumours occurring in testis (testicular germ cell tumours) exhibit a remarkably high expression of the TLS signature. In accordance with these findings, healthy brain tissues express low levels of CXCL12, CXCL13 and CCL21, and brain metastases from melanoma and breast cancer contain no or very few TLSs 58,59 . Other malignancies also presented very low expression of this signature: adrenocortical carcinoma, pheochromocytoma or paraganglioma, and most kidney carcinoma histotypes with the exception of clear-cell renal cell carcinoma.…”
Section: Location Of Tlsssupporting
confidence: 77%
See 3 more Smart Citations
“…This is notably the case for tumours occurring in immunologically privileged sites, such as the brain (glioblastoma and lower-grade glioma) and the eye (uveal melanoma), although tumours occurring in testis (testicular germ cell tumours) exhibit a remarkably high expression of the TLS signature. In accordance with these findings, healthy brain tissues express low levels of CXCL12, CXCL13 and CCL21, and brain metastases from melanoma and breast cancer contain no or very few TLSs 58,59 . Other malignancies also presented very low expression of this signature: adrenocortical carcinoma, pheochromocytoma or paraganglioma, and most kidney carcinoma histotypes with the exception of clear-cell renal cell carcinoma.…”
Section: Location Of Tlsssupporting
confidence: 77%
“…In melanoma, it has been reported that only skin metastases exhibit fully developed TLSs with proliferating B cells and AID expression; by contrast, FDCs were detected in some lung, muscle and gut metastases but not in brain metastases 58 . In breast cancer, analysing a large cohort of 355 metastases from 4 metastatic sites (lung, liver, brain and ovary), Lee et al 59 reported that TLSs can be found in lung and liver metastases but not in brain and ovarian metastases.…”
Section: Clark Level Of Invasionmentioning
confidence: 99%
See 2 more Smart Citations
“…In breast cancer, TLO detection is recently becoming even more relevant as there are correlations between TLOs and other, therapeutically relevant infiltration patterns [48,49].…”
Section: Application To Biomedical Contextmentioning
confidence: 99%